Pengaruh Matakuliah Kewirausahaan dan Praktik Kewirausahaan Terhadap Minat Berwirausaha (Studi Kasus Alumni Febi UIN SU Tahun 2021-2023) - Suci Maharani Pane (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to determine the effect of entrepreneurship courses and entrepreneurial practices on entrepreneurial interest in a case study of FEBI UINSU alumni in 2021-2023. This study applies an associative quantitative approach method that seeks to find a causal relationship between the variables studied. The research population was all FEBI UINSU alumni in 2021-2023 totaling 3951 people. The research sample was determined using the Accidental Sampling technique, where the respondents selected were alumni who could be reached and were willing to participate in this study, with a total of 100 respondents. Data were collected using an online questionnaire via Google From to FEBI alumni in 2021-2023. The results of the analysis show that: 1) Entrepreneurship courses have a significant positive effect on Entrepreneurial Interest with a Tcount value = 9.888> Ttable = 1.984 and significant 0.001 <0.05; 2) Entrepreneurship Practices have a negative but significant effect on Entrepreneurial Interest Tcount = -2.324 <Ttable = -1.984 and significant 0.002 <0.05; 3) simultaneously, Entrepreneurship courses and Entrepreneurship Practices have a significant effect on Entrepreneurial Interest Fcount = 49.587> Ftable = 3.09 and significant = 0.001 <0.05. The R2 value of 0.505 shows that 50.5% of the variation in entrepreneurial interest can be explained by courses and entrepreneurial practices, while the rest is influenced by other factors outside the model